Seroprevalence study of HCV among hospitalized intravenous drug users in Ahvaz, Iran (2001-2006) - Seyed Mohammad Alavi; Leila Alavi (Elsevier, 2009)
Summary: Background and aims: Prevalence of hepatitis C virus (HCV) in intravenous drug users (IDU) varies in different areas according to socioeconomic and geographical circumstances. The present study was performed to determine seroprevalence of HCV in IDU individuals in Ahvaz, Iran. Materials and methods: 142 IDU patients were included in this retrospective study in Ahvaz southwest Iran from 2001 to 2006. Patients were placed in two groups determined by HCV Ab positive or negative status. Data were analyzed using SPSS for Windows (version 11.5; SPSS Inc., USA) software. Results: Out of total 142 cases, 74 persons (52.11%) had a positive HCV-Ab test according to the ELISA method. There was no difference in age, sex, level of education, residency and co-infection with HIV and hepatitis B virus between HCV-Ab positive (HAP) and HCV-Ab negative (HAN) groups (p > 0.05). HCV-Ab positivity was significantly related to imprisonment and duration spent in prison [OR: 3.22, 95% (CI) 2.61-3.76, p < 0.0001]. Conclusion: Patients with IDU constitute a high-risk group for acquisition of HCV infection. Transmission of HCV via sharing syringe and needle as well as blood transfusion has been a significant source of hepatitis C infection for patients with intravenous drug addiction. Keywords: Intravenous drug user, Hepatitis C virus, Seroprevalence, Ahvaz